The Role of Botanic Gardens in Species Recovery :: The Oblong Woodsia as a Case Study - Lusby, Phil; Dyer, Adrian; Lindsay, Stuart (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2003)
A translocation experiment to reintroduce the rare fern Woodsia ilvensis (L.) R.Br. to former sites in England and Scotland is described. The demands of this kind of conservation work brings the work of scientists and horticulturists together. High losses of transplants are to be expected and in order to gradually build up populations in the wild, translocation programmes may have to adopt a multi-phased approach. The facilities at botanic gardens are well suited to this type of conservation work.